Solutions manual for Microeconomic theory - prepare by Chiaki Hara; Ilya Segal; Steve Tadelis
A Solutions Manual, containing solutions to all end-of chapter questions for MICROECONOMIC THEORY by Mas-Colell, Whinston and Green. It is supplied only to those who are adopting the text, and is free